The Investigation of Illocutionary Acts Uttered by the Characters tn the Brave Movie - Dezas Perdani, Yella (Bina Nusantara University, 2023)
The research aimed to determine the sorts and most prevalent illocutionary acts used by the characters in the Brave animated movie. The illocutionary act was defined as the purpose for which the speaker utters something. The research focused on the main character and the entire conversation between each character in the movie. The research applied a qualitative method where the data were taken from the script uttered by all of the characters in the Brave movie who uttered the illocutionary acts. The data collection technique was done in five steps; made the data analyzing format, watched the movie and searched the script, read the script repeatedly, identified the utterances, and classified the utterances and meaning into the illocutionary act. The basic theory used was the illocutionary act proposed by Searle and Austin. There were 85 illocutionary acts found in Brave movie, and it was divided into five classifications: representative, directive, expressive, declarative, and commissive. The result shows that there are 10 (11,76%) representative acts, 42 (49,41) directive acts, 0 the commissive act, 19 (22,35%) expressive acts, and 10 (11,76%) declarative acts. As a result, directives are the illocutionary acts that predominate in Brave movie.